2011
DOI: 10.3390/molecules16064438
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antimicrobial Activities of Methanolic Extracts of Leaf, Stem and Root from Different Varieties of Labisa pumila Benth

Abstract: A local herb, Kacip Fatimah, is famous amongst Malay women for its uses in parturition; however, its phytochemical contents have not been fully documented. Therefore, a study was performed to evaluate the phenolics, flavonoids, and total saponin contents, and antibacterial and antifungal properties of the leaf, stem and root of three varieties of Labisia pumila Benth. Total saponins were found to be higher in the leaves of all three varieties, compared to the roots and stems. Leaves of var. pumila exhibited si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 40 publications
3
98
3
Order By: Relevance
“…32 The result of this study was found to be higher than the findings of Karimi et al. [33][34][35] Although they are from a similar research group, a broad range of rutin content (4.60-116.85 µg/g extract) was observed. Hence, the variance in rutin content is not only attributed to the solvent system, but also the extraction conditions such as temperature, time and extraction method, as well as the variety and maturity stage of the herb.…”
Section: Reflux Extraction For Plant Crude Extractcontrasting
confidence: 56%
“…32 The result of this study was found to be higher than the findings of Karimi et al. [33][34][35] Although they are from a similar research group, a broad range of rutin content (4.60-116.85 µg/g extract) was observed. Hence, the variance in rutin content is not only attributed to the solvent system, but also the extraction conditions such as temperature, time and extraction method, as well as the variety and maturity stage of the herb.…”
Section: Reflux Extraction For Plant Crude Extractcontrasting
confidence: 56%
“…L. pumila is plentiful in resorcinols, flavonoids and phenolic compounds, i.e. gallic acid, myrecetin, kaempherol and catechin (36)(37)(38). These bioactive phytochemicals equip the plant with anti-proliferative activity against prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…alataroot and stem (300 mg/disc) indicated direct inhibitory action againstBacillus subtilis and Bacillus cereus (Gram-positive bacteria) with inhibition zone ranging from 0.79-0.94 cm while Enterobacter aerogenes, Escherichia coli and Klebsiella pneumonia (Gram-negative bacteria) with inhibition zone ranging from 0.50 to 1.11 cm. 28 The antimicrobial activity is due to the presence of gallic acid and myricetin from phenolic and flavonoid compounds, respectively. Melastoma malabathricum L.(Melastomataceae family).…”
Section: Antimicrobial Activity Of Malaysian Plantsmentioning
confidence: 99%